Crop Ontology Governance and Stewardship Framework - Arnaud, Elizabeth; Hazekamp, Tom; Laporte, Marie-Angélique; Antezana, Erick; Andres Hernandez, Liliana; Pot, David; Shrestha, Rosemary; Dreher, Kate; Castiblanco, Valheria; Menda, Naama; Fabio Guerrero, Alberto; Hualle, Vilma; et al. (2022)
A governance & stewardship framework for the Crop Ontology Project is required as this is a collaborative tool developed by a Community of Practice. Over the last 12 years of its existence, it has increased significantly in scope and use. Collecting and storing plant trait data and annotating the data with ontology terms is widely accepted by the crop science community to be critical to enable data interoperability and interexchange through tools such as the Breeding API (BrAPI). The Crop Ontology Community of Practice is organised around roles, curation principles and validation processes that require a formal description. A governance framework is defined by the various actors involved in the asset’s design, development and maintenance. It is complemented by a quality assurance process to ensure that trust levels, value creation, and sustainability objectives meet appropriate quality levels. The general principles underlying data governance are integrity, transparency, accountability and ownership, stewardship, standardization, change management and a robust data audit.